Virtual Reality (VR) for teaching and learning human anatomy in secondary school / Muhammad Razieq Roslan and Chew Chiou Sheng - Roslan, Muhammad Razieq; Chew, Chiou Sheng (College of Computing, Informatics, and Mathematics, 2024)
Human anatomy teaching has evolved significantly, transitioning from tedious rote memorization to more engaging and immersive approaches facilitated by technological advancements. Traditional methods often needed help to convey the intricate 3D nature of human anatomy, leading to difficulties in comprehension and engagement among students. However, recent developments, particularly in virtual reality (VR) technology, have revolutionized anatomy education. This research project focuses on designing, developing, and evaluating a VR-based educational tool, "Humanatomy VR," aimed at secondary school students. The tool offers an immersive and interactive learning experience, allowing students to explore anatomical structures in a three-dimensional environment while receiving detailed explanations. Through storytelling techniques, developing Humanatomy VR transcends conventional teaching methods, providing a memorable and engaging learning experience. Evaluation of the tool's usability using System Usability Scale (SUS) questionnaires yielded positive feedback from 15-year-old Form Three students at Sekolah Menengah Kebangsaan Putrajaya Presint 16(1) with an average score of 86.25%, indicating high levels of accessibility and enjoyment. Future recommendations include making the game compatible with various devices, simplifying it with tutorials, and adding engaging content driven by the players.